Island bodies: registers of race and 'Englishness' on Tristan da Cunha c.1811 - c.1940 - Rousset, Thierry Jean-Marie (Department of Historical Studies, 2018)
Tristan da Cunha, a small island in the South Atlantic, is perhaps best known today as the remotest inhabited island in the world. Historical scholarship relating to the island has either focused on its supposed insularity, or has completely elided it in the broader thematic and theoretical studies that often dominate scholarship of the Atlantic world. By placing Tristan da Cunha and metropolitan Britain together within the same analytic field and using an interdisciplinary approach, this work traces metropolitan representations of the island from c.1811-c.1940. Part One traces the ways in which Tristan da Cunha was drawn into the European geographic imagination as well as the economic networks and channels of global circulation during the era of mercantile capitalism. This process saw the island framed as a Romantic English rural idyll displaced into the South Atlantic, and resulted in a metonymic linkage being created between the island body and the bodies that inhabited it. The shift from mercantile capitalism to industrial capitalism and the rise of modernity in the metropole led to (re)negotiations regarding who formed part of the social body of the metropole and Part Two traces the impact of this shift on the island body(ies) of Tristan da Cunha. The (re)negotiation and (re)constitution of the island body(ies) as a result of new metropolitan optics and debates regarding race, degeneration, social belonging, and bourgeois norms resulted in the increasing nativisation and concurrent racialisation of the islanders in metropolitan representations. The island bodies became both coloniser and colonised, Briton and nativised other, Anglo-Saxon and racialised other. These discourses - the island as Romantic English rural idyll, or as isolated, degenerating and inhabited by nativised others - would coexist from the turn of the nineteenth century. They sometimes cut across one another, at other times they reinforced one another, only to diverge and then cut across one another once again. This work unpacks the polyphonic and often contradictory registers of race and Englishness in these metropolitan representations. At the same time it unsettles and attempts to reconstitute the dominant lenses through which the island has previously been analysed.